Body Stalk Anomaly - Nicolae Gică; Livia Mihaela Apostol; Iulia Huluță; Anca Maria Panaitescu; Ana Maria Vayna; Gheorghe Peltecu; Nicoleta Gana (Diagnostics, 2024)
Abdominal wall defects encompass three primary classifications: gastroschisis, omphalocele and anomalies resembling body stalk. Potential causative factors include early amnion rupture, amniotic bands, vascular disruptions or abnormal folding of the embryo. The prevalence of these defects stands at 1 in 14,000 live births. Body stalk anomaly is characterized by a substantial abdominal defect coupled with spine and limb anomalies, along with a very short or absent umbilical cord. We present a case of a rare abdominal defect known as body stalk anomaly, the most severe form of this spectrum of diseases. The diagnosis of this anomaly was established during the first trimester of pregnancy. Subsequently, the patient opted for pregnancy termination and chose not to undergo genetic testing. The anatomo-pathological results confirmed the findings. Body stalk anomaly is not compatible with life; therefore, early identification and understanding the clinical implications of this rare anomaly for informed decision-making in prenatal care are very important.